Graded Derived Equivalences - Bo-Ye Zhang; Ji-Wei He (Mathematics, 2021)
We consider the equivalences of derived categories of graded rings over different groups. A Morita type equivalence is established between two graded algebras with different group gradings. The results obtained here give a better understanding of the equivalences of derived categories of graded rings.